Comparison of point reactor response and space-dependent core response. (November 2020) - Anghel, V.N.P.; Li, L.; Atfield, J.E.; Yaraskavitch, L.R.; Sur, B.
Highlights: Experiments were performed in the ZED-2 reactor at low frequency less than 100 rad/s. The imaginary parts of the normalized space dependent and the point reactor transfer are very close to each other. This behaviour is shown in both experiment and for two group diffusion models. This type of comparison may allow one to choose between different delayed neutron data available in literature. Abstract: The space dependent reactor core transfer functions differ from the point reactor transfer functions that have no spatial dependence. During experiments using different perturber and detector positions, it was found that the imaginary part of the ZED-2 reactor core transfer function approximates better the imaginary part of the point reactor transfer function than the corresponding complete transfer function does. This behavior is found to be robust, being replicated by two group diffusion models with parameters close to those of the reactor. The approximate correspondence of the imaginary parts of the measured and of the point reactor transfer functions was used to compare two available choices of delayed neutron data. The results of this comparison are consistent with comparisons using independent methods. The comparison of the imaginary parts might be used in some cases to choose the most appropriate delayed neutron parameters from several available options.